Inhibitory synaptic plasticity: spike timing-dependence and putative network function - Vogels, Tim P.; Froemke, Robert C.; Doyon, Nicolas; Gilson, Matthieu; Haas, Julie S.; Liu, Robert; Maffei, Arianna; Miller, Paul; Wierenga, Corette; Woodin, Melanie A.; Zenke, Friedemann; Sprekeler, Henning (Frontiers in Neural Circuits, 2013)
While the plasticity of excitatory synaptic connections in the brain has been widely studied, the plasticity of inhibitory connections is much less understood. Here, we present recent experimental and theoretical □ndings concerning the rules of spike timing-dependent inhibitory plasticity and their putative network function. This is a summary of a workshop at the COSYNE conference 2012.